Cardiovascular Magnetic Resonance in patients with HIV Infection : assessing the structural and functional abnormalities associated with remodelling of the myocardium - Stoltz, Anton Carel (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.